The German Press about Russian Foreign Policy Activities: The Crisis in Ukraine (2013–2014) and its Consequences - Z. Z. Bahturidze; D. S. Rachkova (Управленческое консультирование)
The article is devoted to identifying the current image of Russia in the mirror of the German media after the Ukrainian crisis. The role of the media is noted, the crisis situation in Ukraine is characterized. Analyzed publications in the leading print media of Germany on the topic of Russian foreign policy in Ukraine and the role of the Russian Federation in the political crisis in Ukraine (2013–2014). The authors have identified and identified key approaches in the formation of German society a certain idea of Russia and its foreign policy. As conclusions, it is noted that both for objective reasons, and not least thanks to the German media, which use a lot of negative characteristics when constructing the image of Russia, relations between the Russian Federation and the Federal Republic of Germany go through a zone of mutual exclusion. However, relations between the Russian Federation and the Federal Republic of Germany can go to a new level, taking into account the possible pragmatic cooperation of the two states, and provided, among other things, a reduction in the degree of anti-Russian rhetoric in the German media.